The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1002/2014jb011029
|View full text |Cite
|
Sign up to set email alerts
|

Thermal perturbations beneath the incipient Okavango Rift Zone, northwest Botswana

Abstract: We used aeromagnetic and gravity data to investigate the thermal structure beneath the incipient Okavango Rift Zone (ORZ) in northwestern Botswana in order to understand its role in strain localization during rift initiation. We used three-dimensional (3-D) inversion of aeromagnetic data to estimate the Curie Point Depth (CPD) and heat flow under the rift and surrounding basement. We also used two-dimensional (2-D) power-density spectrum analysis of gravity data to estimate the Moho depth. Our results reveal s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
78
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(89 citation statements)
references
References 87 publications
11
78
0
Order By: Relevance
“…Analyzing and integrating these data will enable the development of a complete picture of this early-stage rift and extract valuable constraints on continental rifting processes. We expect that our study will strongly complement previous, ongoing, and future studies in this and other parts of the EAR, including the Project for Rift Initiation Development and Evolution (PRIDE) (Bufford et al, 2012;Leseane et al, 2015;Yu et al, 2015).…”
Section: Summary and Future Workmentioning
confidence: 54%
“…Analyzing and integrating these data will enable the development of a complete picture of this early-stage rift and extract valuable constraints on continental rifting processes. We expect that our study will strongly complement previous, ongoing, and future studies in this and other parts of the EAR, including the Project for Rift Initiation Development and Evolution (PRIDE) (Bufford et al, 2012;Leseane et al, 2015;Yu et al, 2015).…”
Section: Summary and Future Workmentioning
confidence: 54%
“…Some authors add the OG as the terminus of the southwestern extension branch (e.g. Scholz et al, 1976;Modisi et al, 2000;Leseane et al, 2015). As this southwestern extension branch is poorly defined, we name the region from the EARS in the east, Lake Upemba in the north and the OG in the southwest, the South-Western Extension Area (SWEA).…”
Section: Earsmentioning
confidence: 99%
“…Crust models for the OG area are proposed by two local studies based on seismic receiver functions (Yu et al, 2015b) and aeromagnetic and gravity data (Leseane et al, 2015). Both studies indicated a thinned crust beneath the OG relative to the adjacent crust although they suggest different magnitudes for the thinning (4 to 5 km and 10 to 12 km respectively).…”
Section: From the Crust To The Mantlementioning
confidence: 99%
“…Advective heating by migrating magmas might affect larger volumes of the lithosphere in case of continued magmatic activity. Heating of the lithospheric mantle and crust by migration of hot mantle fluids focused in Precambrian lithospheric shear zones has been invoked, for instance, to explain the shallow Curie temperatures, which imply temperatures of >500°C at depths of 8-15 km, and high heat flows (60-90mWm -2 ) observed in the incipient Okavango Rift Zone in southern part of the East African rift (Leseane et al, 2015). However, though it may be important atop plumes and in arcs, the actual contribution of heat advection by migrating melts in heating the lithosphere is still poorly constrained.…”
Section: Accepted Manuscriptmentioning
confidence: 99%